Social sustainability in industry 4.0. Challenge for the EU-2030 - Sierra Benítez, Esperanza Macarena (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
By 2030, the year in which Industry 4.0 will be fully established in European society, Europe must overcome great challenges if it does not want to lose that combination of democracy, social rights and an advanced state of well-being that somehow has become its trademark. In order to meet these challenges, the EU can count on two lines of action: the international area (trade agreements, EUAfrica Alliance, 2030 Agenda), and the EU itself (European pillar of social rights). We understand that it is essential that trade agreements not only include clauses that ensure compliance with certain standards regarding the environment and work environment, but that also guarantee their effectiveness (for example, through ILO supervision). Likewise, to ensure the effective application of the European pillar of social rights, it is necessary to provide sufficient normative instruments to guarantee its compliance.
Keywords: social protection; international agreements; European Pillar of social rights; social sustainability; Industry 4.0